ANALISIS MODEL PEMBELAJARAN PADA MATERI BANGUN RUANG DI KELAS V SEKOLAH DASAR: SYSTEMATIC LITERATURE REVIEW - Niki Azura (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to identify and analyze learning models applied in delivering spatial geometry material in grade V of Elementary School. This study uses a quantitative descriptive approach with the Systematic Literature Review (SLR) method. The data sources in this study are national journal articles obtained from electronic databases indexed in Google Scholar, with publications ranging from 2020 to 2025. Data collection techniques include the stages of data collection, data analysis, and drawing conclusions. The data analyzed are the results of primary studies that have been published in the form of scientific articles. Based on the results of the analysis, it was found that the selection of an appropriate learning model can support teachers in achieving learning objectives and be an effective strategy to improve student competence.